The Sinews of Peace, 1948 - Churchill, Winston S. (Post-War Speeches., 2014)
The first volume in this captivating collection of the prime minister's speeches brings to life the heady days after V-Day-and a nation newly at peace. Legendary politician and military strategist Winston S. Churchill was a master not only of the battlefield, but of the page and the podium. Over the course of forty books and countless speeches, broadcasts, news items and more, he addressed a country at war and at peace, thrilling with victory but uneasy with its shifting role on the global stage. In 1953, he was awarded the Nobel Prize for Literature for "his mastery of historical and biographical description as well as for brilliant oratory in defending exalted human values." During his lifetime, he enthralled readers and brought crowds roaring to their feet; in the years since his death, his skilled writing has inspired generations of eager history buffs. The Sinews of Peace was the alternate title of the 1946 "Iron Curtain Speech" delivered at Westminster College-in which Churchill championed the idea of a "fraternal association" between people of the English-speaking world to preserve the spirit of military and political cooperation forged during the war. President Truman was in the audience. Was Churchill proposing a formal alliance between the two world powers' This inspiring collection contains the first of Churchill's speeches delivered immediately after World War II. In his signature charismatic, impassioned style, he calls for unity and cooperation between the victims and the limping former Axis powers-including a partnership between Germany and France. These speeches both recounted history and made it, as the leaders of Europe convened to form a new world order.